Outcomes of Heart Failure–Related Hospitalization in Adults with Congenital Heart Disease in the United States. (16th November 2012) - Rodriguez, Fred H.; Moodie, Douglas S.; Parekh, Dhaval R.; Franklin, Wayne J.; Morales, David L.S.; Zafar, Farhan; Adams, Gerald J.; Friedman, Richard A.; Rossano, Joseph W.
Abstract Background Heart failure (HF) accounts for >3 million hospital admissions annually in adults with acquired cardiovascular disease, but there are limited data on HF admissions in adults with congenital heart disease (ACHD). The purpose of this study was to test the hypotheses that HF admissions are common in ACHD and associated with significant morbidity and mortality. Methods The 2007 Nationwide Inpatient Sample was used to assess national prevalence, morbidities, and risk factors for mortality during hospitalizations among ACHD with HF. Results Of the 84 308 (95% CI 71 345–97 272) ACHD admissions in the United States in 2007, 17 193 (95% CI 14 157–20 229) had a diagnosis of HF (20%). ACHD with HF was associated with an increased risk of death compared to ACHD without HF (OR 3.3, 95% CI 2.6–4.1). On multivariable analysis independent risk factors for mortality included nonoperative intubation (OR 6.1, 95% CI 3.3–11.4), sepsis (OR 4.3, 95% CI 2.4–7.4), and acute myocardial infarction (OR 3.2, 95% CI 1.8–5.7). Cardiac defects associated with an increased risk of mortality included ventricular septal defects (VSDs) (OR 1.8, 95% CI 1.0–3.4). Conclusions In this large population‐based study, HF‐related hospitalizations were common in ACHD and associated with an increased risk of death compared to non‐HF admissions. The risk of mortality is increased with the diagnoses of VSDs and the presence of specific comorbidities such as respiratory failure and sepsis.